(untitled) (Journal of actual problems of jurisprudence, 2023)
This article aims to clarify the essence of legal pluralism, which is a prerequisite for adopting legal pluralism in human rights law. This is particularly important because the use of the term «legal pluralism» in human rights law varies from one proponent to another, making it difficult to specify what legal pluralism is in the first place. This article identifies the roots of the concept of legal pluralism by tracing the origins of the debate on legal pluralism to answer the question: what should be included in the «legal order» when discussing legal pluralism? The study on the origin of legal pluralism shows that non-state legal orders were always the subjects of the discussion, deducing that it is natural that those non-state legal orders become the object of legal orders in the study of legal pluralism in human rights law discipline. In this study, legal pluralism is considered not only from a theoretical and legal point of view but also from a historical and legal point of view, which can enrich any scientific work. In legal doctrine, the research category appeared relatively recently, about 50 years ago, which was the logical result of the collapse of the colonial system and the emergence of the need for newly independent states ensuring the coexistence of historically established norms of ordinary law with colonial law, distributed by metropolises. Evidence was provided regarding the change in the concept of legal pluralism over time. Keywords: legal pluralism, human rights, law, state, freedom.